2014
DOI: 10.3945/ajcn.113.072793
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin intake correlates with hearing thresholds in the older population: the Korean National Health and Nutrition Examination Survey

Abstract: Dietary intake of vitamin C was associated with better hearing in the older population. Because less than one-half of elderly participants in this study consumed a sufficient amount of vitamins, and vitamin intake decreased with age, we should consider proper diet counseling to prevent hearing decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…It includes about 10,000 individuals each year as the survey sample and collects information on socioeconomic status, health-related behaviors, quality of life, healthcare utilization, anthropometric measures, biochemical and clinical profiles for noncommunicable diseases and dietary intakes with three component surveys: health interview, health examination, and nutrition survey. Kang et al [19] analyzed the data of 3,253 adults between 50 and 80 years old using the 2011 KNHANES database and found that dietary intake of vitamin C was associated with better hearing in the older population. Kang et al [5] analyzed the data of 16,554 subjects of the 2009–2011 KNHANES database and concluded that metabolic syndrome was associated with increased hearing thresholds in women, and CKD was associated with increased hearing thresholds in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…It includes about 10,000 individuals each year as the survey sample and collects information on socioeconomic status, health-related behaviors, quality of life, healthcare utilization, anthropometric measures, biochemical and clinical profiles for noncommunicable diseases and dietary intakes with three component surveys: health interview, health examination, and nutrition survey. Kang et al [19] analyzed the data of 3,253 adults between 50 and 80 years old using the 2011 KNHANES database and found that dietary intake of vitamin C was associated with better hearing in the older population. Kang et al [5] analyzed the data of 16,554 subjects of the 2009–2011 KNHANES database and concluded that metabolic syndrome was associated with increased hearing thresholds in women, and CKD was associated with increased hearing thresholds in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…This survey is an ongoing cross-sectional survey of the civilian population living in households aged ≥1 year of South Korea and described in elsewhere. [16][17][18] A field survey team that included an otolaryngologist, an ophthalmologist and nurse examination unit performed interviews and physical examinations. Individuals selected underwent a basic health assessment that included blood pressure measurements, blood and urine collection, pulmonary function test and dental examination, ophthalmologic examination and otolaryngological examination.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Histories of exposure to explosives or occupational noise were classified as positive or negative, as previously described [14]. Briefly, an explosive noise was defined as a sudden loud noise such as an explosion or gunshot.…”
Section: Methodsmentioning
confidence: 99%